PENGELOLAAN BUDAYA SEKOLAH SEHAT DI MADRASAH IBTIDAIYAH NEGERI SEKUDUK KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Yusida, Elly; sukm, Sukmawati; Suib, Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This study aims to obtain comprehensive information on the management of a healthy school culture in MIN Sekuduk Kecamatan Sejangkung Sambas Regency, which is related to planning, implementation, evaluation of healthy school culture. This research is descriptive qualitative research. The data sources consist of principals, UKS coordinators, classroom teachers, committee chairmen, hygiene coordinators, financial managers and learners. The results show that: 1) The planning of healthy school culture management in MIN Sekuduk Sejangkung Sub-district is well planned. 2) Implementation shows that implementation of TriS UKS program (health education, health service and healthy environment development) 3) Evaluation of the management of healthy school culture in MIN Sekuduk Sejangkung Sub-district has been running well it can be argued that the principal has made policies for the realization of a healthy school culture, a positive influence on the behavior of school residents and communities around the school and give awards to participants Students who behave in a healthy life in school.Keywords: Management, Culture, Healthy School.